Innovative processes in tourism of Ukraine - Lysiuk, Tetiana V.; Bezsmertniuk, Taras P.; Tereshchuk, Oksana S.; Biletskyi, Yurii V.; Pasichnyk, Mykhailo P.; Ierko, Iryna V.; Demianchuk, Olena H. (My University, 2023)
The purpose of the article is to determine the features of innovation processes in the tourism industry of Ukraine. To conduct an objective and thorough study, the following methods were used: abstract and logical; analysis and synthesis; system analysis; method of analogies; method of expert evaluations. The content of innovations and innovative activity is characterised, the main types of innovative technologies in the activities of tourism enterprises are considered. The main factors influencing the introduction of innovative technologies are highlighted, namely: the adverse impact of macroeconomic shocks, increased flow of financial risks, lack of own financial resources, low innovation activity in the service sector in Ukraine. It is determined that strategic management of innovations is important for service enterprises, which improves both entrepreneurial and professional economic management.
Keywords: Innovation; innovation process; innovative activity; innovative technologies; tourism; tourist enterprise